Determinants of Language Choice among Bilingual Students in Kazakhstani Educational Institutions - Алдабердикызы, А. (Eurasian Journal of Philology Science and Education, 2015)
The article investigates such sociolinguistic aspects of the modern Kazakhstani society like a language prestige, the change of linguistic behavior of learners of different educational institutions. The author will try to compare the domains of first and second language use by students before and after their moving to an urbanized place in the Republic of Kazakhstan with the purpose of getting high education in universities or colleges. The article is based on the data of official reports and the results of the research work conducted by the author herself. The results of the research will demonstrate the curve of language preference and change in bilingual educational system of Kazakhstan.Мақала заманауи Қазақстанның қоғамының тілдік мәртебе, тілдік қылықтың ауысуы тәрізді әлеуметтік-лингвистикалықаспектілерін қарастырады. Мақала авторы урбандалған қалаға жоғарғы немесе орта мамандандырылған білім алу мақсатында келген оқушы-студенттердің бірінші және екінші тілді қолдану аяларын салыстыруға тырысады. Мақалада мемлекеттік мекемелердің ресми мәліметтерімен қоса, автордың жеке ғылыми зерттеу жұмыстарының нәтижелері де қолданылған. Бұл нәтижелер Қазақстанның қостілді білім беру саласындағы тілдік таңдау мен тілдік артық көру мәселесінің қисық сызығын байқауға мүмкіндік береді.